Klasifikacija ključnih besed iz bibliografskih enot - Korošec, Andrej (Organizacija znanja, 2012)
Bibliographic data from the Slovenian researchers from COBISS (Cooperative Online Bibliographic System) discussed research area is not easily identifiable. The data from which can be seen research interests are the key words. The goal we set ourselves the classification (grading) keywords bibliographic research units. As a classifier we chose SRA classification. To achieve best results, we paid special attention to the selection and preparation of texts for machine learning. For the classification of keywords bibliographic research units, we used tool for data mining called "Oracle Data Miner." We chose the method of support vector machines, which are successfully used in the classification of texts.
Keywords: bibliografske enote; klasifikacija; metoda podpornih vektorjev; podatkovno rudarjenje; raziskovalci; rudarjenje besedil; SVM